Experimental Evidence on the Formation of Ethene through Carbocations in Methanol Conversion over H‐ZSM‐5 Zeolite. Issue 34 (14th July 2015) - Wang, Chao; Yi, Xianfeng; Xu, Jun; Qi, Guodong; Gao, Pan; Wang, Weiyu; Chu, Yueying; Wang, Qiang; Feng, Ningdong; Liu, Xiaolong; Zheng, Anmin; Deng, Feng
Abstract The methanol to olefins conversion over zeolite catalysts is a commercialized process to produce light olefins like ethene and propene but its mechanism is not well understood. We herein investigated the formation of ethene in the methanol to olefins reaction over the H‐ZSM‐5 zeolite. Three types of ethylcyclopentenyl carbocations, that is, the 1‐methyl‐3‐ethylcyclopentenyl, the 1, 4‐dimethyl‐3‐ethylcyclopentenyl, and the 1, 5‐dimethyl‐3‐ethylcyclopentenyl cation were unambiguously identified under working conditions by both solid‐state and liquid‐state NMR spectroscopy as well as GC‐MS analysis. These carbocations were found to be well correlated to ethene and lower methylbenzenes (xylene and trimethylbenzene). An aromatics‐based paring route provides rationale for the transformation of lower methylbenzenes to ethene through ethylcyclopentenyl cations as the key hydrocarbon‐pool intermediates.